Rancangan Teknologi RFID Gerbang Parkir Pada UINSU Medan - Ramadhan, Muhammad Rizky; Lesmana, Reza Kurnia; Siregar, Fahreza Shiddiq; Ridho, Rasyid; Isnan, Muhammad Hafi Isfahan (Jurnal Sains dan Teknologi (JSIT), 2023)
RFID (Radio Frequency Identification) is an identification method using a barcode or magnetic card and an RFID reader as the reading media. This research is based on the results of observations and previous studies that aim to design RFID for parking gates at Tuntungan North Sumatra State Islamic University. Data collection uses the Observation method. The results of this study aim to determine the success of the RFID design at the gates of Tuntungan North Sumatra State Islamic University. Testing has been carried out through prototype trials. This research focuses on the success of the gate design of the Tuntungan North Sumatra State Islamic University, which aims to facilitate access in and out of the gate in order to reduce parking queues.